Can 5d and sp impurities be magnetic? - N. Papanikolaou; N. Stefanou; R. Zeller; P.H. Dederichs (Physical Review Letters, 1993)
We present a systematic study of local spin moments of impurities in alkali-metal hosts, by means of ab initio, local-spin-density electronic structure calculations. Our results predict for the first time that besides the well-known cases of 3d and 4d impurities also 5d and some sp impurities are magnetic in the alkali metals both on substitutional and interstitial positions.